Substance use and associated factors among Debre Berhan University students, Central Ethiopia - Tesfay Birhane Gebremariam; Kalayu Birhane Mruts; Tedla Kutaye Neway (BMC, 2018)
Abstract Background Being a global burden of youths, substances use is unhealthy behavior that exposes youths to health and social problems. Knowledge of the prevalence and predictors of substance use behavior among university students is important for designing periodic and locally appropriate interventions. This study is conducted to assess the prevalence and predicators of substances among Debre Berhan University students. Methods Cross-sectional quantitative study was employed in May 2016. Stratified two-stage sampling technique was applied to choose 695 students. Substance use behaviors were assessed using tools derived from World Health Organization Model Students' Substance Use Core Questionnaire. Result The lifetime utilization of alcohol, khat and cigarette among students was found to be 36.3%, 10.9% and 7.4% respectively. The lifetime utilization of shisha and cannabis was 4.2% and 4.5% respectively. About 17%, 5.7%, and 3.1% of students are currently using alcohol, Khat and Cigarette respectively. Using multivariate binary logistic regression, being male, feeding out of the university café, being from private preparatory school, having higher monthly income, having substance user families and friends were found to be variables significantly associated with students' substance use behaviors. Conclusions The current prevalence of substances use among Debre Berhan University students is low comparing to other Ethiopian and African universities. Youth are starting substance use at lower grades especially at preparatory schools. Substance use behaviors are affected by complex factors at individual, family, school, social, and environmental factors. Therefore, strategies to alleviate youth substance use problems should focus on changing individual perception, knowledge, and intention towards substances. There is a need for further research with more powerful sample size and weighted estimates using complex analysis. Reasons for lower prevalence of substance use from other Ethiopian universities shall be further explored using qualitative study.